Inverters with Different Loads for Ring Oscillators True Random Number Generator Analysis - Hashim N.A.N.; Loong J.T.H.; Hamid F.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
CMOS integrated circuits; Electric inverters; Memristors; Metals; MOS devices; Nanoelectronics; Number theory; Oxide semiconductors; Random number generation; SPICE; Complementary metal-oxide-semiconductor technologies; Hardware and software; Memristor; Multilevels; Physical phenomena; Ring oscillator; Security issues; True randoms; Hardware security